2009
DOI: 10.1073/pnas.0911376106
|View full text |Cite
|
Sign up to set email alerts
|

Differences in human and chimpanzee gene expression patterns define an evolving network of transcription factors in brain

Abstract: Humans differ from other primates by marked differences in cognitive abilities and a significantly larger brain. These differences correlate with metabolic changes, as evidenced by the relative up-regulation of energy-related genes and metabolites in human brain. While the mechanisms underlying these evolutionary changes have not been elucidated, altered activities of key transcription factors (TFs) could play a pivotal role. To assess this possibility, we analyzed microarray data from five tissues from humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
166
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 42 publications
8
166
0
Order By: Relevance
“…Moreover, over one-third of transcription factor genes differentially expressed between human and chimpanzee brains encode ZNF transcription factors (20). It has been proposed that these genes function as master regulators of transcriptome evolution and could contribute to the transcriptional and phenotypic differences between humans and nonhuman primates (18,20). Our results reveal Alu exonization as an important mechanism in the lineage-specific regulatory evolution of ZNF genes.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Moreover, over one-third of transcription factor genes differentially expressed between human and chimpanzee brains encode ZNF transcription factors (20). It has been proposed that these genes function as master regulators of transcriptome evolution and could contribute to the transcriptional and phenotypic differences between humans and nonhuman primates (18,20). Our results reveal Alu exonization as an important mechanism in the lineage-specific regulatory evolution of ZNF genes.…”
Section: Discussionmentioning
confidence: 63%
“…Approximately 25% of ZNF genes in the human genome are primatespecific, and the majority of ZNF gene groups with primatespecific expansion were subject to strong positive selection according to nonsynonymous/synonymous substitution rate (dN/ dS) analysis (18). Moreover, over one-third of transcription factor genes differentially expressed between human and chimpanzee brains encode ZNF transcription factors (20). It has been proposed that these genes function as master regulators of transcriptome evolution and could contribute to the transcriptional and phenotypic differences between humans and nonhuman primates (18,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus interesting to note that remarkably elevated levels of TE activity have been recorded in the brain (Erwin et al, 2014), that a higher range of KRAB-ZFPs is expressed in the brain than in most other adult human tissues , and that KRABZFPs disproportionately contribute to differences between the brain gene networks of chimpanzees and humans (Nowick et al, 2009). These observations suggest that the endovirome and its KRAB-ZFP controllers could have played an important role in the expansion of higher brain functions that were key to the emergence of modern humans.…”
Section: Discussionmentioning
confidence: 99%
“…Functional genomics also provides a means to probe human and non-human cells directly for differences in regulatory regions and gene expression (Nowick et al, 2009;Somel et al, 2011), which can then be traced back to genetic determinants. For example, combined analysis of human and chimpanzee gene expression data and sequences suggested that pain perception and nociception may have changed in humans through differential regulation of opioid signaling (Cruz-Gordillo et al, 2010).…”
Section: The Next-generation Sequencing Eramentioning
confidence: 99%